Oleuropein enhances proteasomal activity and reduces mutant huntingtin-induced cytotoxicity - Huang, Zih-Ning; Lee, Sin-Yi; Chen, Jie-Mao; Huang, Zih-Ting; Her, Lu-Shiun (Frontiers in Pharmacology, 2024)
Huntington's disease (HD) is a hereditary neurodegenerative disease that primarily affects the striatum, which is responsible for movement control. The mutant huntingtin (mHtt) with an increased length of polyQ stretch is prone to aggregate. The mHtt aggregates accumulated in neurons are the primary cause of neuropathology in HD. Thus far, no effective cure for HD has been developed. Polyphenols are natural antioxidants that provide neuroprotection in neurological disorders. Here, we provide evidence to show that oleuropein, the main polyphenol compound in olive leaves and olive oil, increased cell viability in the HD cell models -STHdh Q7/Q7 striatal cells and N2a cells ectopically expressing truncated mHtt, and STHdh Q111/Q111 striatal cells expressing the full-length mHtt. In both HD model cells, oleuropein effectively reduced soluble and aggregated forms of mHtt protein. Interestingly, oleuropein-associated reduction of mHtt aggregate was linked to increased proteasome activity but not the autophagic flux. Oleuropein appeared to modulate the proteasome activity via an unidentified pathway because the 20S proteasome catalytic β subunits and proteasome regulator PA28γ, as well as multiple MAPK pathways were not affected. In summary, we demonstrated that oleuropein enhances the degradation of mHtt by increasing proteasomal protease activities and alleviates mHtt-induced cytotoxicity. Hence, we propose that oleuropein and potentially other polyphenols are promising candidates for alleviating HD.